The Effect of Pimpinella Anisum and Origanum Vulgare Extracts Against Streptococcus Sanguinis, Streptococcus Mutans, and Streptococcus Salivarius - Fatemeh Lavaee; Armin Moqadas; Farzan Modarresi; Massoumeh Nowrouzi (Journal of Dentistry, 2022)
Statement of the Problem: There are global efforts for introducing a new herbal antimicrobial agent with minimal side effects. There are some reports about the antimicrobial properties of Pimpinella anisum and Oregano Vulgare. Purpose: In this study, the antimicrobial properties of Pimpinella anisum and Oregano Vulgare have been assessed. Material and Method: In this experimental in vitro study, the dental plaque samples were collected from children aged 3 to 5 years old who were referred to a private dental office with diagnosis of dental caries. After determination of the bacterial colonies of Streptococcus sanguinis, Streptococcus mutans and Streptococcus salivarius, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ethanolic and methanolic extracts of Pimpinella anisum and Oregano vulgare were measured by macrodilution and microdilution methods. Results: The mean MIC and MBC of Pimpinella anisum extract and Oregano vulgare extract and their combination against Streptococcus mutans, Streptococcus sanguinis, and Streptococcus salivarius were statistically different (p< 0.001). The combination of these extracts showed the lowest MIC and MBC. Conclusion: Hydroalcoholic extracts of the Pimpinella anisum and Oregano Vulgare were effective antibacterial agent against Streptococcus mutans, Streptococcus salivarius, and Streptococcus sanguinis so the combination of these two extracts showed the highest antibacterial properties on all the bacteria evaluated.